Os empreendimentos hidrelétricos na Amazônia e os peixes migradores : barragens e reservatórios como potenciais impactantes ao sucesso reprodutivo dessas populações. - Vasconcelos, Lilian Paula (2017)
The implementation of hydropower projects is one of the greatest threats to fish diversity worldwide, especially in tropical rivers, where many high commercial value species migrate hundreds of kilometers in response to flood pulses. The interruption of river connectivity, caused by the electric impoundments, compromises the connection among habitats that are indispensable for the life cycle of these species, and may negatively affect both their reproduction and recruitment. In this context, the Amazon basin, which contains the largest freshwater fish diversity on the planet, is being heavily threatened due to the increasing construction of hydroelectric power plants. Thus, the objective of this study was to evaluate the reproductive activity of the large migratory Amazonian catfish of the genus Brachyplatystoma after the construction of two hydroelectric plants (Santo Antônio and Jirau) on the Madeira River, Brazilian Amazonian; and, to verify, by generalized linear models adjustment, if the reservoir of Santo Antônio dam has acted as a barrier to the descending movements of ichthyoplankton.